Freeze-dried macroporous foam prepared from chitosan/xanthan gum/montmorillonite nanocomposites - Liu, Huihua; Nakagawa, K.; Chaudhary, Deeptangshu; Asakuma, Y.; Tade, Moses (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2011)
Freeze-dried macroporous foams were prepared from an aqueous colloidal suspension of chitosan/xanthangum/Na+-montmorillonite nanoclay (MMT). The suspension formed gel structure as a consequence of freezing, named cryogel. Cryogel is defined as a gel formed due to the concentration increase of the substrates caused by the ice formation during freezing. This obtained cryogel was subsequently dried under vacuum condition to produce porous foam materials. Two freezing methods were employed in the present work in order to investigate the influence of the processing on sample characteristics, namely; contact freezing with a heat exchanger and immersion freezing in a cryo-bath. Based on the SEM observation, in the case of contact freezing; rapid freezing (−2 C/min) resulted in randomly aligned pores as compared to the pore alignment obtained in the case of slow freezing (−0.25 C/min); the mean pore size for rapid freezing and slowing freezing were 40 μm and 68 μm, respectively. However, in immersion freezing samples, aligned and bamboo-like straight structures with pore layer spacing of 22 μm were observed. The different microstructures significantly influenced the mechanical hardness of the prepared foams nanocomposites. The MMT dispersion within the bionanocomposites was found to be characteristically exfoliated from X-ray diffraction and electron microscopy analysis. Small angle X-ray diffraction data indicated that the polymeric networks were modified by the exfoliated MMT and the MMT also improved the hardness of the prepared foams.